A correlation study between hyperthyroidism and some apoptosis markers among Iraqi patients - Maaroof, Zainab A.; Ibraheem, Shaima R.; Ibrahim, Aida H. (Iraqi Journal of Science, 2021)
This study was carried out in the Center of Endocrinology and Diabetes in Baghdad during the period between October 2019 to February 2020. The aim was to measure the level of some apoptosis markers and some autoimmune antibodies related to the thyroid gland in Iraqi patients with hyperthyroidism and evaluate the correlation between all the measured parameters. The study included 88 patients who were divided into three groups; group 1 included 30 newly diagnosed hyperthyroidism patients (24 females, 6 males); group 2 included 30 patients of hyperthyroidism who were under treatment (28, 2 males); group 3 included 28 healthy individuals as control group (22 females, 6 males). Most of the patient’s ages ranged between 40 to 60 years (73.3%), while60.7% of the control group were within the same age category. The highest rate of disease was in females compared with males (86.7% vs. 13.3%). The current study included 30% of newly diagnosed hyperthyroid patients and 30% of patients undergoing treatment for a while. The majority of the hyperthyroidism patients, both newly diagnosed and treated, were overweight, and they accounted for 53.3% of each group. Highly significant differences (p=0.001) were found in the level of TNF-α in the newly diagnosed and under treatment patient groups in comparison with the level in the control group. The results show a significant decrease in TNF-α level in the treated patients as compared to its levels in the other groups, which indicates that this factor is affected by the given therapy. It was found that 25% of the patients with hyperthyroidism were suffering from diabetes, with a significant correlation (p=0.009) between hyperthyroidism and diabetes mellitus. It was observed that these patients have a significant increase (p=0.038) in the level of p53 as compared to its level in patients with non-diabetic hyperthyroidism patients and healthy subjects. This study shows a non-significant negative correlation between TNF-α and TSH levels (r= -0.06) and a non-significant positive correlation between TNF-α and p53 levels (r= 0.17) in hyperthyroidism patients. The positive correlations between some apoptosis markers and anti-TSHR antibodies and between TSH and these antibodies in hyperthyroidism patients refers to an increase in the concentration of apoptosis markers, which may lead to an increase in the levels of thyroid autoantibodies, which affects thyroid tissue potency and increases thyroid hormone production.